Removal of malachite green by sugarcane bagasse biochar using response surface methodology - Mohamad, M. (2019)
This study focus on the adsorption of malachite green (MG) dye using sugarcane bagasse biochar as adsorbent. Agricultural waste of sugarcane bagasse turned into low cost and eco-friendly biochar adsorbent was studied. Batch adsorption studies were carried out to analyse the effect of operating conditions which include contact time (10 to 45 minutes), adsorbent dosage (0.01 to 0.05 g) and initial concentration (10 to 40-mg/L) on the percentage of MG removal. Optimisation studies were conducted using response surface methodology (RSM) by employing central composite design (CCD). The correlation coefficient, R 2 for MG removal was found to be at 0.9878. Three dimensional (3D) surface graph and contour plot were used to analyse the interaction effect between parameters. The optimum conditions for MG removal which predicted by RSM were found to be at contact time of 42.26 minutes, adsorbent dosage of 0.05 g and initial concentration of 39-mg/L which resulted in MG removal of 99.47 at desirability of 1.000. Â© 2019 Author(s).